SOSIALISASI PENGELOLAAN SAMPAH ORGANIK MELALUI BUDIDAYA MAGGOT BSF DI DESA JEMBAYAN DALAM, KALIMANTAN TIMUR - Mohammad Sumiran Paputungan; Viddo Try Anggoro; Ramli Ramli; Dayang Nathasya Aurelia Putri Awari; Ence Alya Vira Azizah; Jemi Irlanda Haikal; Norma Gupita; Azwar Pramucti; Ahmad Nabillah Ramadhan; Chella Nur Kumala; Nurul Tri Oktavia; An Nisa Octavia (Universitas Mataram, 2022)
Currently, the people in Desa Jembayan Dalam have only been trained about processing organic waste based on the concept of composting. However, the practice had not been sustained due to wasting time in the process of composting organic waste to become a usable product. The knowledge of the people in Desa Jembayan Dalam on organic waste management is still limited. This community service activity aimed to introduce people about the application of organic waste treatment by using black soldier fly (BSF) larvae and to foster the interest of people in processing organic waste using BSF larvae/maggots. The activity was held in Jembayan Dalam Village on July 14, in the form of capacity building through a socialization event about maggot BSF. Participants were given an understanding of the BSF life cycle, the cultivation process of BSF maggots, the types of organic waste as larvae feed, and the by-product produced at the end of the larvae treatment process. The event was attended by 25 people from Dusun Lembonang, Desa Jembayan Dalam. Six participants were interested in rearing BSF eggs that had been provided. There were six participants who tried to raise the BSF maggot from the eggs of BSF maggot that had been provided. However, only one participant succeeded in raising it for two weeks. The type of organic waste that she used was waste from onion skin and vegetables that already decaying. The length of the BSF maggot that was successfully maintained reached 2 cm. Most participants showed interest in BSF maggot cultivation because of its role in reducing organic waste and its products that can be used as poultry feed. Limited free time owned by the people in the village is an obstacle for them to practice BSF maggot cultivation.